2005
DOI: 10.1088/1126-6708/2005/03/039
|View full text |Cite
|
Sign up to set email alerts
|

Topological mass term in effective Brane-World scenario with torsion

Abstract: In this work we investigate a braneworld scenario where a Kalb-Ramond field propagates, together with gravity, in a five dimensional AdS slice. The rank-2 KalbRamond field is associated with torsion. We study the compactification of the KalbRamond field to four dimensional space-time without gauge fixing, focusing on the effects of torsion. On the brane the Kalb-Ramond field interacts with A µ -gauge and scalar matter fields. We analyze the propagators of this theory and as an application investigate the consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…It is interesting to note that in our work we take the antisymmetric background tensor field B µν = 0 for simplicity, but its importance is very well known from the point of view of the (super)string theories where it was first associated with massless modes [41] and, recently, the presence of such a background for the string dynamics has a very important implication in non-commutativity of the spacetime [42], and in many supergravity models [43]. Recently, a careful analysis of the B µν field in a five-dimensional brane-world scenario where it was associated with torsion was made [44]. The result of this analysis showed that it is possible to construct a topological configuration like a static cosmic string on the brane whose formation involves only the zero mode.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that in our work we take the antisymmetric background tensor field B µν = 0 for simplicity, but its importance is very well known from the point of view of the (super)string theories where it was first associated with massless modes [41] and, recently, the presence of such a background for the string dynamics has a very important implication in non-commutativity of the spacetime [42], and in many supergravity models [43]. Recently, a careful analysis of the B µν field in a five-dimensional brane-world scenario where it was associated with torsion was made [44]. The result of this analysis showed that it is possible to construct a topological configuration like a static cosmic string on the brane whose formation involves only the zero mode.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the detection of cosmic strings could be a possible way to verify the inflationary paradigm, providing an interesting testing ground into string theory by probing the braneworld scenario before the inflationary phase [29][30][31][32]. Many other publications have investigated the effects of braneworld gravity on the physics of cosmic strings [34][35][36][37][38][39]. Specifically in [39], the authors have studied the consequences of the braneworld modified gravity on the cosmic string phenomenology.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the detection of cosmic strings could be a possible way to verify the inflationary paradigm, providing an interesting testing ground into string theory by probing the braneworld scenario before the inflationary phase [29,30,31,32]. Many other publications have investigated the effects of braneworld gravity on the physics of cosmic strings [34,35,36,37,38,39]. Specifically in [39], the authors have studied the consequences of the braneworld modified gravity on the cosmic string phenomenology.…”
Section: Introductionmentioning
confidence: 99%